Some aspects of the fishery and biology of Polydactylus indicus (Shaw) - Nayak, P D (Indian Journal of Fisheries, 2016)
One of the commercially important fisheries of the Bombay and Saurashtra waters is that of Polydactylus indicus locally known as 'Dara'. PreUminary observations on the biology and fishery of P. indicus have been recorded by Mohamed (1955). The food and feeding habits of this species are described by Karekar and Bal (1958). The present investigations were undertaken with a view to obtaining more information regarding the fishery and biology of this important species. This paper deals with the data collected on the catches of trawlers working from Bombay, during the years 1950-57, supplemented by observations made at a few of the other centres where a good fishery for this fish exists. During this period different types of trawlers were operating from Bombay. Taiyo Mam No. 17 operated Otter-trawl from 1951-54. The Cutters M.T. Ashok and M.T. Pratap used Ottertrawls during 1950-53 and then they together formed into a pair of Bulltrawlers from 1953-57. In addition to these, two more pairs of Bull-trawlers, namely, Satpati-Pilotan and Arnalla-Paj started operating during 1956-57.